Cost of capital : applications and examples - Pratt, Shannon P.; Grabowski, Roger J. (Hoboken, N.J. : Wiley, 2010)
'Cost of capital estimation has long been recognized as one of the most critical elements in business valuation, capital budgeting, feasibility studies, and corporate finance decisions and is also the most difficult procedure to assess and perform. Now in its fourth edition, Cost of Capital: Applications and Examples addresses the most controversial issues and problems in estimating the cost of capital.''Renowned valuation experts and authors Shannon Pratt and Roger Grabowski present both the theoretical development of cost of capital estimation and its practical application to valuation, capital budgeting, and forecasting of expected investment returns encountered in current practice. In this learning text/handy reference, Pratt and Grabowski deftly review and explore the theory of what drives the cost of capital, the models currently in use to estimate cost of capital, and the data available as inputs to the models to estimate cost of capital.''In this thoroughly updated and comprehensive fourth edition, Cost of Capital summarizes the results and practical implications of the latest research--much of which is gleaned from unpublished academic working papers--and includes scores of formulas and elucidating examples throughout to enhance readers' insights.''The landmark book corporate treasurers, business appraisers, CPAs, and valuation experts have come to rely on, Cost of Capital lays out the basic tools to use immediately when estimating cost of capital or when reviewing an estimate. This dynamic author team also analyzes criticism of major models for developing estimates of the cost of capital in use today, and also presents procedures for a number of alternative models.''This definitive text is an indispensable reference tool for professional valuation practitioners as well as attorneys and judges, investment bankers, CFOs, academicians and students, and CPAs.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Capital investments; Business enterprises -- Valuation; Capital investments -- United States; Business enterprises -- Valuation -- United States